Based On Longitudinal Distance Of Sloped Column Working Bodies Working Between Garden Rows (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In the article, when working with a plow-softener that works flat without a tiller, the longitudinal and transverse positions of the working bodies in relation to the frame depend on the resistance to the traction created during the working of the working bodies. the results obtained from experimental studies are presented.